2016
DOI: 10.1186/s40064-016-2519-4
|View full text |Cite
|
Sign up to set email alerts
|

Automated volumetric breast density estimation out of digital breast tomosynthesis data: feasibility study of a new software version

Abstract: BackgroundA new software version of VolparaDensity (Volpara Algorithm version 1.5.1) is capable of calculating volumetric breast density (VBD) using either full-field digital mammography (FFDM) or digital breast tomosynthesis (DBT) images. In this preliminary study, we evaluated the feasibility and consistency of this new automated software.FindingsRaw data from both DBT and FFDM were acquired from women breast cancer screening at our institution between April and August 2015 using. The DBT and FFDM images obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
13
1
2
Order By: Relevance
“…Volpara version 1.5.1 is able to derive volumetric MD from the central projection and compressed breast thickness. A feasibility study using paired DM and DBT images obtained during one compression (136) demonstrated near perfect agreement for calculated breast volume, but small though statistically significant differences for dense volume and hence VBD. Other groups have used a similar modelling approach to derive VBD using each of the DBT projections, again with closer agreement between VBD derived from MRI and DBT than between DM and either DBT or MRI (137).…”
Section: Dbt and Synthetic 2d Dmmentioning
confidence: 95%
“…Volpara version 1.5.1 is able to derive volumetric MD from the central projection and compressed breast thickness. A feasibility study using paired DM and DBT images obtained during one compression (136) demonstrated near perfect agreement for calculated breast volume, but small though statistically significant differences for dense volume and hence VBD. Other groups have used a similar modelling approach to derive VBD using each of the DBT projections, again with closer agreement between VBD derived from MRI and DBT than between DM and either DBT or MRI (137).…”
Section: Dbt and Synthetic 2d Dmmentioning
confidence: 95%
“…para uma mama padrão e corrige o efeito de combinações anodo/filtro diferentes de Mo/Mo, respectivamente. O fator de conversão (c), responsável por corrigir para porcentagens de tecido adiposo e glandular diferente de 50%/50% não é utilizado, visto que o software usa a densidade específica de cada paciente no lugar de (c) [15].…”
Section: Methodsunclassified
“…Finalmente, a DVM é obtida pela razão entre o volume denso e o volume total da mama. Posteriormente, o software utiliza a DVM específica de cada paciente para cálculo da DGM de maneira individualizada [15].…”
Section: Introductionunclassified
“…Ng and Lau 7 have identified six requirements (denoted in their paper as "sanity checks") that should be fulfilled by an automated breast density measurement software: Some studies exist that validate existing software applications for automated breast density assessment. [14][15][16][17][18][19] Typical aspects assessed by these studies are accuracy (comparing measured breast density to an objective ground truth), reproducibility (see Ng and Lau's requirements 1 to 5), consistency (see Ng and Lau's requirement 6), and agreement with visual assessment (comparing classified breast density to a subjective reference).…”
Section: Automated Breast Density Assessmentmentioning
confidence: 99%